Optimalisasi Peran Guru dalam Peningkatan Kreativitas Siswa Melalui Pembelajaran Seni Budaya: Penelitian - Khoirul Minarti; Novi Nitya Santi; Abdul Aziz Hunaifi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the role of teachers in enhancing students' creativity through art and culture learning at SDN Gedangsewu 1 Pare. Using a qualitative approach with a case study design, data were collected through in - depth interviews, participatory observations, and documentation. The findings show that teachers act as facilitators, motivators, and innovators by applying contextual and project-based learning strategies. These approaches include the use of recycled materials, integration with other subjects, and encouragement of student expression. Despite limited facilities and training, teachers overcame challenges through creativity and collaboration with parents. Art learning positively influenced students' originality, flexibility, and self-expression. This research contributes to the development of educational practices by emphasizing the importance of teacher roles and contextualized learning in fostering creativity. The findings are expected to serve as a reference for educators and policymakers in designing inclusive and creative learning environments in primary education.